A Study of Consumer Behavior in Adoption of Technology-Based Product - Fachira, Ira; Nasution, Reza Ashari (SBM ITB, 2007)
This paper aims at describing factors that influence consumer intention to use new technology and how these factors interact with each other. The Academic Information System of the School of Business and Management ITB was selected as the unit of analysis and the Unified Theory of Acceptance and Use of Technology model was used to identify the degree of acceptance of different groups of users to the systems and the factors that influence their intention to use it. This study involves different user groups (students and lecturers). To provide further understanding of consumer behavior in technology adoption, Structural Equation Modeling will be used to test simultaneous effect of the factors in the model.Â Keywords: technology acceptance, Academic Information Systems, consumer behavior